Feminist Intersectionality Centering the Margins in 21st-Century Medieval Studies - Seal, Samantha; Nolan Sidhu, Nicole (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book gathers contributions negotiating feminism's place within medieval studies. It is about overlaps and twists, about the inseparability of multiple means of critique - ecocriticism and disability studies, art history and race studies, legal history and modern activism - from a feminist perspective. The feminist scholarship in this book moves in many different directions and examines the medieval past (and its role in the present) from many different angles. What remains consistent throughout is the dedication to reconfiguring medieval studies, a commitment not to be content simply with adding women on as an extra in conventional European patriarchal accounts, or with analyzing gender in history or literature without fundamentally re-envisioning the intellectual foundations upon which those fields of study have been built. Previously published in postmedieval Volume 10, issue 3, September 2019.
Keywords: Europe -- History -- 476-1492.; Women -- History; Literature, Medieval; History of Medieval Europe; Women's History / History of Gender; Medieval Literature